Utilization of Family Planning Services in Karnali Academy of Health Science, Jumla - Shrestha, Sharmila; Chaulagain, S.; Pandey, K. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Family planning is an integral part of maternal health as its uptake is a significant factor in the reduction of maternal mortality and in ensuring positive child health outcomes specially in developing countries, however, its usage remains low. Objectives: To describe prevalence and pattern of contraceptive use, among women accessing family planning facilities. Study design: A retrospective review of hospital records of family planning clinic clients at the teaching hospital was conducted. Results: Total 2811 clients accepted a family planning service during the period. Contraceptive prevalence rate was 21%. Modal age group of clients (81%) was below 20 years old. Injection Depo was the most common method (69%) and implant was less used method (8%) among the temporary method of family planning. Conclusion: There is an identified need for promotion of uptake of family planning methods. Involvement of young women, uneducated women and men in contraception counseling and services is essential to improve its uptake and continuity.